83rd Annual Meeting of the Eastern Psychological Association - I A Novikova; E Yu Chebotareva; A L Novikov (Peoples' Friendship University of Russia (RUDN University), 2012)
A brief review of the International Program of the 83rd Annual Meeting of the Eastern Psychological Association (EPA) that took place on 1-4 March 2012 in Pittsburgh (USA) is submitted in the publication.